2022
DOI: 10.1002/ddr.21962
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights on [1,2]oxazolo[5,4‐e]isoindoles on multidrug resistant acute myeloid leukemia cell line

Abstract: A series of [1,2]oxazolo [5,4-e]isoindole derivatives was evaluated against HL-60 cell line and its multidrug resistance (MDR) variant, HL-60R, resistant to doxorubicin and to other P-gp substrates by overexpressing the efflux pump. They displayed antiproliferative activities, with IC 50 values ranging from 0.02 to 5.5 µM. In particular, the newly synthesized compound 4k produced synergistic effects in terms of cell growth inhibition and cell death induction either in combination with a Vinca alkaloid, Vinblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Cancer is a leading disease worldwide, and the projections indicate that the global incidence of cancer will continue to rise [ 1 , 2 ]. The conventional anti-cancer agents are losing their efficiency [ 3 ], highlighting the need to introduce new anti-cancer entities [ 4 , 5 , 6 ]. One strategy to address the issues with existing chemotherapeutics is molecular hybridization: a strategy that generates more efficient therapeutics by combining two (or more) pharmacophores or two (or more) entire drugs in a single hybrid molecule that addresses one or multiple targets [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a leading disease worldwide, and the projections indicate that the global incidence of cancer will continue to rise [ 1 , 2 ]. The conventional anti-cancer agents are losing their efficiency [ 3 ], highlighting the need to introduce new anti-cancer entities [ 4 , 5 , 6 ]. One strategy to address the issues with existing chemotherapeutics is molecular hybridization: a strategy that generates more efficient therapeutics by combining two (or more) pharmacophores or two (or more) entire drugs in a single hybrid molecule that addresses one or multiple targets [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several RTKs are mutated or overexpressed in human cancers and are likely to be involved in constitutive activation of survival and proliferative signaling, and thereby, disease progression [ 2 ]. Therefore, inhibition of RTKs has become an attractive approach for the treatment of several cancers [ 3 , 4 ]. However, the development of primary and secondary resistance to RTK-targeted therapies limits its clinical application [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules show several advantages as they typically possess fast distribution throughout the body, rapid clearance, and target accumulation at the tumour site. During our studies aiming at the development of new bioactive heterocyclic compounds (Spanò et al 2021a , b ; Barreca et al 2022b ; Cilibrasi et al 2022 ; Labbozzetta et al 2022 ), we explored several classes of PSs, and some of them showed high potency, with outstanding selectivity index versus tumour cells inducing mitochondrial apoptotic death (Spanò et al 2017 ). We recently reported our studies on two classes of small heterocyclic compounds, namely pyrimido[5,4- g ]indolizines 1 and pyrimido[4,5- c ]pyrrolo[1,2- a ]azepines 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules show several advantages as they typically possess fast distribution throughout the body, rapid clearance, and target accumulation at the tumour site. During our studies aiming at the development of new bioactive heterocyclic compounds (Spanò et al 2021a, b;Barreca et al 2022b;Cilibrasi et al 2022;Labbozzetta et al 2022), we explored several classes of PSs, and some of them showed high potency, with outstanding selectivity index versus Abstract Nineteen pyrrolo [1,2-h][1,7]naphthyridinones and pyrido [2,3-c]pyrrolo [1,2-a]azepinones were synthesized as new tricyclic systems in which the pyridine ring is annelated to the 6,7-dihydroindolizin-8(5H)-one and 5,6,7,8-tetrahydro-9H-pyrrole[1,2-a]azepine-9-one moieties to obtain potential photosensitizing agents. They were tested for their photoantiproliferative activity on a triple-negative breast cancer cell line, MDA-MB-231, in the dark and under UVA light (2.0 J/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%